СПРИЯННЯ ЗАЙНЯТОСТІ, ЗАХИСТ ВІД БЕЗРОБІТТЯ ТА ДОПОМОГА ПО БЕЗРОБІТТЮ ЗА НОРМАМИ СУЧАСНОГО МІЖНАРОДНОГО ТРУДОВОГО ПРАВА - Назимко, Олена Вікторівна (SUPREMANCE OF LAW, 2018)
The author of this scientific and legal paper presented and considered those present international labor law subject-matter, regulative norms which establish ILO’s key principles, basic purposes and specific tasks on promoting employment, protecting from unemployment and giving dole.